P PENGARUH INFLASI, NILAI TUKAR, DAN SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN - Togatorop, Fibe Chatarina; Yovita, Lenni (Politeknik Bisnis Indonesia, 2024)
The Jakarta Composite Index is a reflection of stock market performance in Indonesia. This research was conducted to find out the effect of inflation, exchange rates, and interest rates on the JCI. This study uses monthly time series secondary data for the period 2014-2023 taken from investing.com, IDX, BPS, and BI. The analysis used multiple linear regression with eviews 12 software. After the analysis, inflation, exchange rates, and interest rates simultaneously affect the JCI. Partially inflation and interest rates do not affect the movement of the JCI. While the exchange rate can affect the movement of the JCI. The results of this study indicate that investors do not pay attention to inflation and interest rates in making investment decisions. The depreciating rupiah exchange rate is a negative signal for investors.